PKM Pelatihan Transformasi Digital Meningkatkan Kinerja Manajemen Sekolah dengan Teknologi Informasi - Wijaya, Andi; Moch Arif Maulana; M. Rial Andrika; Moh. Roby Trio Darmawanto Ikhsan (Yayasan Literasi Altruis Khatulistiwa, 2025)
Digital transformation is an urgent necessity in the field of education to enhance the efficiency and effectiveness of school management. The service partners, namely the principals of Madrasah Tsanawiyah (MTs) in Pujer District, Bondowoso Regency, still face challenges due to administrative processes that are conducted manually and lack integration. Based on preliminary survey results, the utilization level of Information and Communication Technology (ICT) was relatively low, with only around 30% of education staff using digital tools for basic administrative tasks. The most affected aspects include student and teacher data management, financial administration, attendance recording, and activity reporting. This community service program employed a participatory training and mentoring method through four stages: needs analysis, digitalization awareness, training on digital school management applications, and assistance in implementing an integrated information system. The results indicate a significant improvement in ICT adoption, with the use of digital management applications increasing from 30% to 85%. Administrative efficiency improved by 60%, data processing time decreased by 50%, and internal communication became faster and more accurate. Success indicators include enhanced digital competence, increased data management speed, the establishment of an integrated school information system, and sustained technology utilization. This program successfully accelerated digital transformation and improved educational governance quality in MTs within Pujer District